Cross my heart and hope to spy - Carter, Ally (New York Hyperion, 2007)
Cammie Morgan is a CIA legacy and attends the premier school in the world ... for spies. The school hosts some mysterious guests with the code name Blackthorne. When Cammie is blamed for a security breach that threatens to expose the school's top secret status, she and her friends face danger to clear Cammie's name and learn the truth about Blackthorne
1 11
Keywords: Gallagher Academy for Exceptional Young Women (Imaginary place) -- Fiction; Morgan, Cammie (Fictitious character) -- Fiction